(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The study examined the profitability and constraints to Shea butter processing in Mokwa local government area of Niger state. A multistage sampling technique was used to collect data from the 139 respondents. The data were analysed using descriptive statistics, budgeting analysis and five point likert scale. The results revealed that respondents mean age was 54years. Most of the respondents 87(67.58%) were married, very few 2(1.02%) had tertiary education. The cost and returns analysis revealed that an average processor earns about N38620 per month. Variable costs (N2899715) components accounted for about 98% of the total cost. The enterprise has an estimated Benefit Cost Ratio of about 2.82 and an Internal Rate of Returns on investment of about 1.82 indicating that the enterprise is profitable and worthwhile. Poor access to credit facilities and extension contacts were the major challenges facing the processors. The study recommends that the processors should organize themselves into associations and cooperative groups with a view to leverage on group actions to better their access to credit facilities. Also, Government and Research Institutes should ensure that extension activities directed at the Shea butter production and processing get to the end users.